Effects of Treatment with Quercetin on the Quality of Cryopreserved Bovine Semen - Teobaldo Tironi, Stella Maris; Vicente Seixas, Flavio Augusto; de Moraes, Gentil Vanini; Stefanello, Talitha Fernandes; Akashi, Karen Tiemi; Silva Marques, Nayara Fernanda; Nakamura, Celso Vataro; Martinez, Antonio Campanha (Acta Scientiae Veterinariae, 2019)
Background: Semen cryopreservation is one of the most common biotechnologies in the reproduction of animals of agricultural interest, especially bulls. However, cryopreservation can be harmful to sperm cells, with susceptibility to oxidative stress being one of the causes. The addition of antioxidants such as quercetin may inhibit and/or reduce such damage, reducing fertility. Quercetin can increasing sperm motility and interaction capacity between spermatozoa-oocyte, to increase cellular metabolism and reduced DNA fragmentation and oxidation following thawing. Therefore, the objective of this study was to evaluate the protective effect of quercetin on the metabolism of bovine semen following thawing. Material, Methods & Results: Three Brahman bulls in reproduction age and previously considered fit for reproduction were used. The semen samples were collected via the electroejaculation method, and the samples were homogenized to form pooled semen from three ejaculates, which was diluted in Tris-yolk egg-glicerol diluent medium. Quercetin was added to diluent, to final concentrations of 0, 5, 10, 15 and 20 μg.mL-1 in each group. The samples were kept frozen in straws of 500 μL, with concentration of 40,000,000 spermatozoid / mL for 15 days and were thawed in water at 36°C for 30 s. All the tests was performed in five replicates. The cell metabolism status was evaluated by quantification of superoxide radical production with a nitroblue tetrazolium test (NBT) and scanning spectrophotometry. By spermatic evaluation, the following parameters were evaluated via the computerized system of sperm analysis (CASA): total motility (TM, %), progressive motility (PM, %), velocity curved line (VCL, mm/s), velocity straight line (VSL, mm/s), velocity average path (VAP, mm/s), distance curved line (DCL, mm), distance straight line (DSL, mm), distance average path (DAP, mm), amplitude of lateral head displacement (ALH, mm), beat cross frequency (BCF, Hz), wobble (WOB = VAP/VCL), linearity (LIN, VSL:VCL) and straightness (STR, VSL:VAP). And by surface analysis through scanning electron microscopy (SEM). The NBT test demonstrated an increase in cell metabolism of approximately 40% up to the limit of 15 µg.mL-1 quercetin. The parameters of CASA pertaining to velocity (VCL, VSL, VAP) and as a consequence, wobble and linearity increased as a function of the quercetin concentration until 20 µg.mL-1, which was shown to be statistically significant. No significant morphological changes between groups were observed by the SEM technique. Discussion: The reduction of NBT indicates oxidative metabolism, being an indirect measure of the oxygen dependent activity of the cells, therefore the results demonstrate that quercetin supplementation increased the number of cells with high metabolic activity. Regarding the evaluation of CASA, according to the literature, some parameters are reliable estimates of the fertilization capacity of the human spermatozoon, among them, the VCL. In this study, all speeds were increased with Quercetin, including LCV, demonstrating its importance in supplementation in bovine seminal diluent. Scanning electron microscopy evaluates the structural morphology of the cell surface. As with previous results, in this study, all cells lost the acrosome. However, this type of damage was already expected in thawed spermatozoa. In addition, no other significant changes were observed in the morphology of the membrane or other parts of the sperm. In general, the results presented here suggest that the addition of quercetin to the seminal diluent before freezing improve spermatic quality, which manifests itself as faster spermatozoa and may higher fertilization rates.